Respuesta :

Answer: 1 goes with 2 4 goes with 3

Step-by-step explanation:

Answer:

See below in bold.

Step-by-step explanation:

The first one looks like  x + 3 might be a factor. By the Factor Theorem :To check we plug in x = -3 to see if the f(3) = 0.

f(3) = -27 - 27 + 39 + 15 = 0

So x+3 is a factor of  x^3 - 3x^2 - 13x + 15.

x^3 - 2x^2 - x + 2

Because of the last term +2 , it looks like x - 2 might be a factor of this so we evaluate f(2)

f(2) = 8 - 8 - 2 + 2 = 0

So x - 2 is a factor of x^3 - 2x^2 - x + 2 .

x^4 + 3x^3 - 8x^2 + 5x  - 25.

Because of  the - 25 x + 5 could be a factor so try f(-5)

= (-5)^4 - 3* -125 - 8*25 + 5 * -5 - 25  = 0

So x + 5 is a factor of  x^4 + 3x^3 - 8x^2 + 5x  - 25.

Finally we check if (x + 4) is a factor of -x^3 + 13x - 12 :

f(-4) = - (-4)^3 + 13*-4 - 12 = 0.

So x + 4 is a factor of  -x^3 + 13x - 12.

ACCESS MORE